2009
DOI: 10.1007/s10661-009-0882-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in physicochemical properties of coastal waters of Kalpakkam, east coast of India with special emphasis on nutrients

Abstract: A study pertaining to the seasonal variation in physicochemical properties of the coastal waters was carried out at Kalpakkam coast for a period of 1 year (February 2006 to January 2007). It revealed that the coastal water was significantly influenced by freshwater input during North East (NE) monsoon and post-monsoon periods. Concentration of all the nutrients and dissolved oxygen (DO) was relatively high during the NE monsoon, whereas, salinity and chlorophyll-a (chl-a) were at their minimum level during thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 26 publications
7
35
1
Order By: Relevance
“…Salinity varies in different ecosystems according to topography, tides and freshwater inflow (SATHEESHKUMAR; KHAN, 2009). In the present study, lower salinity values were recorded during the monsoon season, which may be due to the dilution of coastal water by the addition of freshwater from the riverine sources (MCLUSKY, 1989;SATPATHY, 1996;KAMALKANTH et al, 2012), whereas higher values were observed during the pre-monsoon season, which could be attributed to low rainfall, decreased fresh water inflow, high temperature and evaporation (KUMAR et al, 2009;KAMALKANTH et al, 2012;SAHU et al, 2012). BESIKTEPE et al (1995) reported that during winter and spring, the salinity of the surface water was slightly higher due to both the circulation caused by winds and reduced water influx.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Salinity varies in different ecosystems according to topography, tides and freshwater inflow (SATHEESHKUMAR; KHAN, 2009). In the present study, lower salinity values were recorded during the monsoon season, which may be due to the dilution of coastal water by the addition of freshwater from the riverine sources (MCLUSKY, 1989;SATPATHY, 1996;KAMALKANTH et al, 2012), whereas higher values were observed during the pre-monsoon season, which could be attributed to low rainfall, decreased fresh water inflow, high temperature and evaporation (KUMAR et al, 2009;KAMALKANTH et al, 2012;SAHU et al, 2012). BESIKTEPE et al (1995) reported that during winter and spring, the salinity of the surface water was slightly higher due to both the circulation caused by winds and reduced water influx.…”
Section: Discussionmentioning
confidence: 45%
“…In the present study, season-wise observation of dissolved oxygen showed an inverse trend to temperature and salinity. Several studies have reported that the greater solubility of oxygen especially during the monsoon season might be due to low temperature and low salinity values (ROCHFORD, 1951;SATPATHY, 1996;PUTHIYA et al, 2009). This is well explained by the significant negative correlation of dissolved oxygen with salinity and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the present study where the lowest nutrient recorded was during winter as a result of strong mixing, low residence time, low fresh water discharge and low biological activities during this season. Nitrite plays an intermediate role in several biological processes such as ammonium oxidation, assimilation and excretion of nitrite by phytoplankton and bacteria (Satpathy et al, 2010). The nitrite concentration in the study area indicated that it's not biogenic; they were mainly produced via the biological processes.…”
Section: Discussionmentioning
confidence: 92%
“…According to Satpathy et al (2010), the distribution and behavior of nutrients in the coastal environment exhibit considerable variations due to rainfall, tidal incursion, quantum of fresh water inflow and biological activities. This agrees with the present study where the lowest nutrient recorded was during winter as a result of strong mixing, low residence time, low fresh water discharge and low biological activities during this season.…”
Section: Discussionmentioning
confidence: 99%
“…Lowest pH of 6.25 was recorded in station 1 during the month of August and October in S1 and highest of 8.3 during February in station 10. These observed variations in pH could be ascribed due to relatively high land drainage and freshwater discharge from other perennial rivers (Satpathy et al, 2009). According to Neschuk et al (2002) the best pH range for rotifers is 6.5-8.5.…”
Section: Resultsmentioning
confidence: 99%